Construction of biodegradable benzobisthiazole-based conjugated polymers with pendant β-cyclodextrin for synergistic mild-temperature chemo-photothermal therapy - Qi Lai; Shaorong Huang; Yu Wu; Bei Hu; Shuilin Chen; Kun Zhang; Yuqin Xu; Xiaoyong Zhang; Guicai Sun; Yulong Ouyang (Materials & Design)
Photothermal therapy has rapidly gained attention as a promising strategy for tumor treatment, owing to its noninvasive nature, ease of operation, high spatial precision, and minimal risk of developing drug resistance. Despite its advantages, the simple and efficient synthesis of photothermal agents (PTAs) that simultaneously exhibit high photothermal conversion efficiency, excellent water dispersibility, low toxicity, biodegradability, and strong therapeutic performance remains a significant challenge. In this study, we successfully synthesized a benzobisthiazole-based conjugated polymer (DPD-CAN-OH) bearing pendant β-cyclodextrin groups via a click condensation reaction. Doxorubicin was subsequently loaded onto DPD-CAN-OH through the formation of a host–guest inclusion complex, resulting in the DPD-CAN-OH-DOX formulation. Characterization results demonstrated that both DPD-CAN-OH and DPD-CAN-OH-DOX exhibit small particle sizes, high water dispersibility, excellent photothermal conversion efficiency, and favorable biodegradability. Biological assays further confirmed that DPD-CAN-OH is associated with low cytotoxicity and good biocompatibility. Notably, DPD-CAN-OH showed significant potential for osteosarcoma treatment by enhancing reactive oxygen species generation and inducing apoptosis in cancer cells. Importantly, the DPD-CAN-OH-DOX complex exhibited markedly superior antitumor efficacy compared to treatment with doxorubicin or DPD-CAN-OH alone, highlighting the therapeutic benefits of combining chemotherapy with photothermal therapy. Considering the straightforward and efficient synthesis process, along with the excellent physicochemical and biological characteristics of the PTAs developed, we believe this work provides valuable new insights into the design and fabrication of multifunctional PTAs for effective cancer therapy.